2020
DOI: 10.3171/2018.8.jns181949
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Medicare reimbursement for neurosurgical procedures: 2000 to 2018

Abstract: OBJECTIVEThere is currently a paucity of literature evaluating procedural reimbursements and financial trends in neurosurgery. A comprehensive understanding of the economic trends and financial health of neurosurgery is important to ensure the sustained success and growth of the specialty moving forward. The purpose of this study was to evaluate monetary trends of the 10 most common spinal and cranial neurosurgical procedures in Medicare reimbursement rates from 2000 to 2018.METHODSThe Physician Fee Schedule L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 13 publications
5
71
2
Order By: Relevance
“…Youssef and Vyas primarily examined Medicare claims for otolaryngology procedures from 2012 to 2016 and found similar down trending reimbursement 8 . Our findings align with trends of decreasing adjusted reimbursement rates for other surgical subspecialties, including neurosurgery, general surgery, and orthopedic surgery 5–7 . Haglin et al showed that the average reimbursement rates for the most common procedures in general surgery decreased by more than 24% from 2000 to 2018 when adjusting for inflation 6 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Youssef and Vyas primarily examined Medicare claims for otolaryngology procedures from 2012 to 2016 and found similar down trending reimbursement 8 . Our findings align with trends of decreasing adjusted reimbursement rates for other surgical subspecialties, including neurosurgery, general surgery, and orthopedic surgery 5–7 . Haglin et al showed that the average reimbursement rates for the most common procedures in general surgery decreased by more than 24% from 2000 to 2018 when adjusting for inflation 6 .…”
Section: Discussionsupporting
confidence: 77%
“…Even without adjusting for inflation, the average Medicare reimbursement rate decreased by 7.0% during the study period. This is significant and different from other specialties in which reimbursement trends have not decreased if inflation is not adjusted for 5–7 . For example, reimbursement for commonly billed general surgery procedures increased by 10.1% when not correcting for inflation 6 .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…[23][24][25] Haglin et al demonstrated that average Medicare reimbursement rates for the most common procedures in neurosurgery decreased by .25% from 2000 to 2018 when correcting for inflation. 25 Similarly, an analysis of Medicare claims for orthopedic surgery published by Eltorai et al showed that, except for removal of an orthopedic implant, common orthopedic procedures showed a decrease in reimbursement from 2000 to 2016. 23 Additionally, previous studies have shown that for more than a decade, physicians have unilaterally absorbed more negative payment pressure than other medical provider stakeholders.…”
Section: Resultsmentioning
confidence: 99%
“…In the past 20 years, several surgical disciplines, including neurosurgery, orthopedics, general surgery, and plastic surgery, have witnessed a steady, significant decline in Medicare reimbursement rates. [3][4][5][6] In contrast, during this period, physician expenses have risen by over 60%. 7 Moving forward, these findings, together with a fluctuating political climate and the absence of a universally accepted payment model for health-related services, may hamper future vitality of the U.S. health care system.…”
mentioning
confidence: 99%